Experimental analysis of solar concrete collector for residential buildings. Issue 6 (3rd May 2021) - Chandrika, V. S.; Karthick, Alagar; Kumar, Nallapaneni Manoj; Kumar, P. Manoj; Stalin, B.; Ravichandran, M.
ABSTRACT: The performance of the solar water heater varies with respect to incident solar radiation, geographical location, and components of the solar water heater such as glazing, absorber material and storage tank. In this work, building-integrated solar water heating system (BISWHS) is fabricated and its output is evaluated by installing it on the roof and façade of the building for azimuth angles 180°, −90°, and 90°. The experimentation is carried out at the Kovilpatti region (9º 11ʹN, 77º 52ʹE), Tamilnadu, India where the climatic conditions are hot and humid. The experiment is carried out at different mass flow rates of 0.004, 0.00625, and 0.00827 kg/s. The result revealed that the mass flow rate of 0.004 kg/s obtained the maximum temperature of 68°C on the flat roof, while the mass flow rate of 0.00625 and 0.00827 kg/s reached 50°C and 47°C between 14.00 hours. In the same way, the experimentation is carried out at the façade at different azimuth angles. Various parameters are analyzed, such as outlet water temperature, ambient temperature, incident solar radiation, thermal efficiency, and exergy efficiency. The mass flow rate of 0.00827 kg/s has yielded the highest efficiency on the façade and roof of the building.